Penerapan Etika Profesi Dalam Meningkatkan Kualitas Pelayanan Pada Perusahaan Bank Rakyat Indonesia (BRI) - Dito Aditia Nasution; Ardyn Sari Sinaga; Lusi Winda Silaban; Kartika Novelia Nababan; Bella Cyintia Maramis; Alya Ramadhani; Andryan Gandung (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Bank BRI has its own written and unwritten rules for conducting its business activities. Another important component the company upholds is professional ethics. Professional ethics are outlined in a code of ethics established by professional organizations to ensure each member acts professionally, fairly, and responsibly. Professional ethics not only regulates individual behavior but also maintains integrity, responsibility, and public trust in a profession. Implementing a professional code of ethics can certainly improve the quality of Bank BRI's service to customers. The case of PT Bank Rakyat Indonesia, Tbk demonstrates that weak integrity and accountability can be detrimental to many parties. The impact not only reduces the company's credibility but also undermines stakeholder trust in banking in Indonesia. The case at PT Bank Rakyat Indonesia, Tbk reflects a crisis in professional ethics involving integrity, independence, and competence.